Play-Based Assessment: Psychometric Properties of an Early Childhood Learning and Development Assessment Battery - Carlos Montoya-Fernández; Pedro Gil-Madrona; Luisa Losada-Puente; Isabel María Gómez-Barreto (MDPI AG, 2024)
This study aims to explore the reliability, construct validity, and content validity of the Child Learning and Developmental Playful Assessment Battery (Batería de Evaluación Lúdica del Aprendizaje y Desarrollo Infantil; BELADI), a quantitative instrument based on the authentic assessment and playful learning principles, the purpose of which is to assess infant learning and development through motor and competitive games as well as storytelling. The sample was composed of 113 children from Albacete (Spain) between 58 and 72 months of chronological age (M = 64.72; SD = 3.671). To explore the content validity, an expert judgement was carried out and the Content Validity Coefficient (CVC) was calculated. The reliability was analysed using the Cronbach's alpha and McDonald's Ω, and an exploratory factor analysis (EFA) was conducted. The results revealed high reliability indexes in each of the developmental domains, and the EFA included 11 items distributed in two factors for the psychomotor domain, 27 items grouped in three factors for the cognitive domain, and 20 items divided into four factors for the socioemotional domain. In conclusion, the study verifies the validity and reliability of the BELADI for the assessment of the infant learning and development through play, which may be used in research, education, and psychopedagogy.